ORGANIZATION OF DISTANCE LEARNING AT BIOLOGY CLASSES - Kofan, I.; Lykholat, Y.; Khatuntseva, S.; Osadcha, O.; Lykholat, T.; Kvitko, M.; Bronnikova, L. I.; Lykholat, O. (Видавництво НДУ ім. М. Гоголя, 2025)
The article reveals the specific features of distance learning at Biology classes using social networks and web-services. The peculiarities of using distance learning tools in the educational process have been outlined, the phenomenon of distance learning as an effective tool of conducing Biology classes using web-services and social networks, which contributes to better assimilation of knowledge and enhances motivation of students for secondary education, was defined. The research methodology is based on the dialectic interaction of the following methods: the comparative method – to identify the opportunities for compiling assignments for secondary school students, grading, commenting upon answers, communicating with pupils in the real-time mode; the activity-based method – allows revealing essential characteristics and dependences, which enable understanding the specific features of the given phenomenon; allows researching characteristics of the organization of distance learning at Biology classes in dynamics, its individual characteristics using the Telegram social network, Google Classroom, Google Forms services; the systemic method – for wholistic comprehension of structuring and revising the covered material throughout the whole academic year; the synergic method – to understand the organization of distance learning at Biology classes as an open system that changes according to the multi-factor interaction of the processes of learning, upbringing and self-education, substantiation of the peculiarities of using distance learning tools in the educational processes, using innovative technologies, in particular, the technology of blended education. It was emphasized that the use of distance learning technologies in the time of the pandemic is a necessary measure. It was substantiated that working with the use of web-services and social networks allows students for secondary education to master educational material without compaction and adjustment of curriculum, which is essential under the COVID-19 pandemic conditions. It was stressed that the Telegram service has the prospects for the implementation in the educational process since it makes it possible to set quick rapport with a class, to solve problems in the shortest possible time, as well as to grade home assignments in order to ensure the maximum quality of pupils’ getting ready for classes. It was noted that conducting classes using the distance learning tools enables enhancement of the motivational component and improvement of the quality of education. Biology classes conducted with the use of social networks and web-services contribute to better acquisition of knowledge by pupils and their motivation. Comparative analysis of using distance learning tools in the educational process proves the effectiveness of using modern social networks and web-services and their active implementation during the COVID-19 pandemic.
Keywords: distance learning; technology of distance learning; organization; Biology class; students for secondary education; web-service; social networks